2018
DOI: 10.2147/copd.s174898
|View full text |Cite
|
Sign up to set email alerts
|

Is COPD associated with periodontal disease? A population-based study in Spain

Abstract: BackgroundPeriodontal disease is more prevalent and more severe among men and women suffering from chronic obstructive pulmonary disease (COPD) compared with healthy adults. The objectives of this paper were to assess the association between periodontal disease and COPD, controlling the effect of sociodemographic characteristics, oral health status, lifestyle variables, and comorbidities. Second, we identified which of the variables analyzed were independently associated with periodontal disease among COPD suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 35 publications
1
28
0
1
Order By: Relevance
“…First, this study employed a cross-sectional design; therefore, causal relationships between the variables could not be established. Consequently, the results should be interpretated with caution [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, this study employed a cross-sectional design; therefore, causal relationships between the variables could not be established. Consequently, the results should be interpretated with caution [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the participants' questions arise from the need to collect information that any person can answer about the state of their teeth and molars. The generalization of National Health Surveys has already been used in other studies published in Spain where the association between periodontal disease and chronic obstructive pulmonary disease was evaluated [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 A recent descriptive study suggested that the prevalence of periodontal disease was higher among those with COPD compared to non-COPD controls. 24 Another case-control study reported that oral health status was associated with selfreported respiratory health. 25 These results confirm the association between periodontitis and COPD.…”
Section: Discussionmentioning
confidence: 99%
“…In this study using a nationally representative population, we could not find any statistically significant association between reduced lung function and the prevalence of chronic periodontitis. Although several studies in the literature evaluated the association between pulmonary diseases and periodontitis [22,23,30], it has not yet been determined how these two maladies affect each other. Evidence of a positive association between COPD and periodontitis comes from a meta-analysis of 14 observational studies [31], where a pooled association OR was reported as 2.08 (95% CI 1.48–2.91).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review study demonstrated that COPD patients suffer from worse periodontal condition [22]. A population-based study reported that the prevalence of periodontal disease was higher among COPD patients compared to non-COPD controls [23].…”
Section: Introductionmentioning
confidence: 99%